Az agrárértelmiség helyzete a 19. század első felében - Vári, András (Szociológiai Szemle, 2024)
Rural intelligence has meant in our period basically the estate stewards of the large and commercially managed agricultural holdings. The group was the third biggest of the educated groups after that of the priests and the lawyers, counting about four-five thousand men in 1847. However, their formation and stabilization as a social group was hindered by three factors:First, the knowledge that they applied was not sufficiently formalized, not esoteric and inaccessible enough to serve as a base for a professionalization strategy, at least not if one compares it with the arcane knowledge of doctors, for example.Second, the estate stewards were servants of the commercially minded but traditionally styled lords, who tried to push them into positions modelled after that of the personal servants, expecting, on the other hand, expert advice and autonomous management skills. As a result, there was a significant discrepancy between the actual life of the stewards and the model that they were expected to conform to. One aspect of this was the relatively high cultural attainment of the stewards in the face of their inability to attend formal training institutes, due to the utter scarcity of the latter.Their third demarcation problem seems to lie in the fact, that in their public appearances, their associations and press, the stewards themselves, though engaging in avid professional discussions, incessantly cultivate a political dimension, a political shadow of whatever seemingly narrowly agrotechnical issue they are addressing. Be it tobacco or manure, they always add a political remark or two. While this might be a consequence of trying to cope with censorship, it creates the impression that our stewards were nothing but the shield-bearers, the assistants of the great political movements (liberal vs. conservative) gripping the country at the time.On all three counts, the group seems to be semi-autonomous, though clearly distinguishable, but still lacking the full legitimation to be called a separate social group. So one either tries to lump them together with other groups that better fit the structuring criteria of modern social science, or accepts the contemporary opinion that did not doubt their separateness and looks for other ways of classification. This is attempted here with respect to the competence of the stewards in cultural domination, or, a la Gramsci, hegemony.The argument is that their social positions called forth skills, like their inclination to be men of letters as a compensation for missing institutes of formal training that served both their peculiar social positions and fitted admirably with a concept of conservative nation building. While stewards politicized the technical issues, the conservative reformers of the time loved to reduce political issues to technicalities, or at least believed in educating and civilizing the nation on a much wider scale than dirty party politics. So the stewards clicked on to the conservative undertaking of nation building as their group project. Indeed, in the course of their putting up and manning the largest non-political associations of the 1840s, most of the original weaknesses of the position of stewards were attended to: pay, prestige, pensions.Unluckily, the 1848 war of Hungarian independence was lost, capitalism was unleashed with a vengeance by an occupying foreign power, the great estates were sold or leased out and their estate stewards dumped on the highways. The discourse that they developed was, however, resurrected by the neoconservative thinking at the end of the 19th century.